Climate Change and Education: From evidence to action - Fitzpatrick, Rachael; Amenya, Donvan; McAleavy, Tony (Education Development Trust, 2024)
Over the past ten years, the world’s poorest countries have experienced nearly eight times as many natural disasters compared to three decades ago. This report considers the impacts of the global climate emergency on school education in low-income countries, and explores how to address the negative consequences it has on learning.

Why East Africa’s education systems must build climate resilience now: Three takeaways from a conference - Mbugua, Ciku; Simmons, Hannah; Barretto, Johnpaul; Barretto, Ciku Mbugua, Hannah Simmons and Johnpaul (EdTech Hub, 2024)
How can education systems build resilience to climate change? EdTech Hub explored this critical question at the inaugural East African Community Education Conference, held in Arusha this August. Discover our key insights in this blog.

Three Take-Aways on Climate Resilience for Education Systems in East Africa - Simmons, Hannah; Mbugua, Ciku; Barretto, Johnpaul (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Getting ahead of climate hazards: Education cannot wait and strategic partners accelerate anticipatory action - Education Cannot Wait (2024)
As world leaders gather for the United Nations General Assembly and Summit of the Future, Education Cannot Wait (ECW) announced two ground-breaking anticipatory action pilots in Pakistan and Somalia.

Innovative finance reshaping cyclone resilience and child-responsive disaster management in Madagascar - UNICEF Climate, Environment, Energy and Disaster Risk Reduction (2024)
In Madagascar, severe cyclones have become an integral part of children’s lives. Between 2000 and 2024, more than 50 tropical storms and cyclones have impacted over six million boys, girls and adults. Given that nearly 60 percent of Madagascar’s population (31 million) is under the age of 25, children and young people bear a disproportionate burden.*This case study shows how UNICEF, the Government of Madagascar and civil society are working together to pilot a ground-breaking, innovative finance solution that includes a child-responsive, parametric risk transfer product for tropical cyclones. The Today & Tomorrow approach aims to reduce child exposure and vulnerability to future shocks and hazards, engage children and young people in solutions and strengthen the essential social systems and services they rely on most. In Madagascar, Cyclones Cheneso, Freddy and Gamane and Tropical Storm Alvaro affected nearly 200,000 students. The case study highlights UNICEF Madagascar and government efforts in the education sector to support these students and build disaster resilience in affected communities.*ACAPS, Madagascar, Cyclone Exposure and Vulnerabilities and UNICEF, Child Climate Risk Index (CCRI).

Choosing our future: Education for climate action - Sabarwal, Shwetlena; Venegas Marin, Sergio; Spivack, Marla; Ambasz, Diego (The World Bank, 2024)

Climate Change Education for a More Sustainable, Just and Gender Equal World - Plan International (Plan International, 2024)

Acting Now for Tomorrow: Addressing Climate Mobility Challenges in Southeast Asia - Ysmael Arriola, Sarah Lou (The ASEAN, 2024)

The Impact of Climate Change on Education and What to Do about It - Marin, Sergio Venegas; Schwarz, Lara; Sabarwal, Schwetlena (The World Bank, 2024)

Investing in Science, Technology, Engineering and Math (STEM) Education to Build Africa’s Resilience Against Climate Change - United Nations (United Nations Office of the Special Adviser on Africa, 2024)

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EduCare: Digital Resilience for Displaced Youth - Gautier, Maya; Ciriello, Raffaele F (Australasian Conference on Information Systems 2024: Digital Futures for a Sustainable Society, 2024)
The ongoing crises of geopolitical conflict and climate change have forced millions of children worldwide into displacement, disrupting their education, mental health, and access to food security. This researchin-progress paper reports on the design and evaluation of a mobile solution, EduCare, which aims to address the intertwined needs of forcibly displaced school-aged children. Building upon previous research, EduCare integrates educational resources, mental health support, and nutritional guidance into a cohesive sociotechnical system. Using a design science research methodology, this paper outlines the development process of EduCare, guided by principles of resilience, awareness, and empowerment. The potential of EduCare to enhance the resilience of displaced youth is explored through scenariobased design and evaluation of its desirability, viability, and feasibility. This work contributes to the information systems (IS) literature by offering a novel approach to supporting the complex needs of forcibly displaced youth through a sociotechnical framework.
Keywords: ⛔ No DOI found

Towards cool cities and communities: Preparing for an increasingly hot future by the development of heat-resilient infrastructure and urban heat management plan - Cui, Yi; Yin, Mingqiang; Cheng, Xiang; Tang, Junqing; He, Bao-Jie (Environmental Technology & Innovation, 2024)
Planning for extreme heat challenges is an urgent task for urban planners, designers, and managers because urban heat is a new normal climate-related challenge for many cities. However, how to integrate existing scientific outcomes and achieve the transformation from research to practice is a critical question. This study aims to frame a heat-resilient infrastructure system and an urban heat management plan (UHMP) to better promote heat solution implementation. This study analyses heat-related challenges, with China as a typical nation with highly urbanized and urbanizing cities, to demonstrate the urgency of preparing for an extreme heat era. This study then elucidates the fundamentals and methods for heat-resilient infrastructure and UHMP development, with a structure of prevention, preparation, mitigation, adaptation, and co-benefits approaches. Heat–resilient infrastructure was framed to ensure that society withstands, responds to, and recovers from heat–related impacts through actions of planning, design, construction, and operation, considering structural measures, non–structural measures, and a co-benefits approach. Furthermore, a UHMP framework was developed by determining the key mission, critical components, and associated agencies. Overall, this study provides planners, designers, and managers with theoretical and methodological frameworks to comprehensively understand heat solutions and increase their implementation capacity.
Keywords: Challenges and opportunities; Heat-resilient infrastructure; Information technology and telecommunication; Preparation, mitigation and adaptation; Structural and non-structural measures; Urban heat management

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
Keywords: _r:AddedByMyEducationEvidence

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen